1996
DOI: 10.3141/1532-10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Concrete with Ground Waste Tire Rubber

Abstract: Because used tires represent an increasingly serious environmental problem in the United States, this study was undertaken to examine the feasibility of using finely ground rubber in Portland-cement concrete. Various percentages of rubber, by weight of cement, were added to a control mix and the effects on the plastic and hardened properties of concrete were investigated. Workability of the mixes was affected, but it was controllable. For hardened concretes, the tests were conducted for compressive strength, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 0 publications
2
30
0
2
Order By: Relevance
“…On the other hand, most authors reported that when the rubber aggregate was added to the concrete, the content of air increased considerably. They also observed that the content of air increased in concrete mixtures with increasing amounts of rubber aggregates [11,16,17]. The increase in W/C ratio increases the slump of the mixtures regardless of the rubber aggregates' rate in the mixtures.…”
Section: Entrained Air and Workabilitymentioning
confidence: 99%
“…On the other hand, most authors reported that when the rubber aggregate was added to the concrete, the content of air increased considerably. They also observed that the content of air increased in concrete mixtures with increasing amounts of rubber aggregates [11,16,17]. The increase in W/C ratio increases the slump of the mixtures regardless of the rubber aggregates' rate in the mixtures.…”
Section: Entrained Air and Workabilitymentioning
confidence: 99%
“…Some physical and mechanical properties, as well as absorption of water by immersion under vacuum, of cement mortars with the addition of tire rubber have been studied. The tire rubber has been used in powder form to minimize the loss in mechanical properties due to tire rubber incorporation, which has been studied worldwide [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Their after effects of compressive and rigidity showed that there is better holding when magnesium oxychloride bond is utilized. They found that basic applications could be conceivable if the elastic substance is constrained to 17% by volume of the total [5]. In [6] created two rubberized concrete mixtures utilizing fine crumb rubber in one mixtures and coarse chipped rubber in the second.…”
Section: Literature Reviewmentioning
confidence: 99%